Effects of relationship marketing on customer loyalty: evidence from budget hotels in Bandaraya Melaka, Malaysia / Imnie Farahainie Mat Jani - Mat Jani, Imnie Farahainie (Faculty of Business and Management, 2017)
Relationship marketing is a good strategy to be used by many firms to maintain a long-term relationship with customers in today’s business environment which is very competitive and challenging. Relationship marketing also can help the marketers to make effective decisions to enhance customer loyalty and create a quality relationship with customers. The main purpose of this study to determine the relationship between relationship marketing dimensions and customer loyalty towards budget hotels in Bandaraya Melaka. Four key dimensions of relationship marketing are considered in this study which are trust, commitment, communication and conflict handling. The study was conducted in Bandaraya Melaka with a sample of 120 respondents. Sampling method used in this study is convenience sampling. Frequencies, Mean, Reliability Analysis, Pearson Correlation Coefficient and Regression were analyzed using SPSS 21 program. The findings revealed that there are positive relationships between these relationship marketing dimensions and customer loyalty. The result shows that conflict handling has the most significant impact on customer loyalty.